A retrospective cohort study examining secondary prevention post stroke in primary care in an Asian setting - Bansal, Vivek (2022)
Stroke is one of the top contributors to burden of disability-adjusted life-years worldwide. Family physicians have key role in optimising secondary prevention following stroke by managing clinical risk factors and promoting overall control in accordance with clinical practice guidelines.